2019
DOI: 10.1108/lodj-03-2019-0142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of managers’ mindset on leadership behavior

Abstract: Purpose The purpose of this paper is to focus on exploring the link between managers’ mindset (fixed vs growth) and their choice of leadership behaviors. Design/methodology/approach The sample was drawn from a proprietary database provided by a global organization that offers 360-degree online leadership surveys. Individuals in management positions provided an assessment of their mindset orientation as well as how often they engaged in various leadership behaviors. Findings Growth-minded managers consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 50 publications
1
16
0
1
Order By: Relevance
“…Moreover, Ju and Oh (2016) found that nurses' resilience was positively correlated with job involvement and organizational commitment. In addition, many studies agreed that sanctioning leadership behaviors, especially those identified with a transformational leadership approach, are necessary to embed the professional behaviors of nurses; positive attitude and involvement of nurses; and the safety and quality of care for patients, thereby improving the institutional outcomes (Kouzes & Posner, 2019;Manning, 2016). In this respect, Abou Hashish (2020) and Abou Hashish and Khatab (2018) suggested that nurse managers should be well trained to maintain a caring atmosphere through integrating the Caritas processes and fair treatment and paying more attention to the work activities and behaviors of their nurses.…”
Section: ± 068mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Ju and Oh (2016) found that nurses' resilience was positively correlated with job involvement and organizational commitment. In addition, many studies agreed that sanctioning leadership behaviors, especially those identified with a transformational leadership approach, are necessary to embed the professional behaviors of nurses; positive attitude and involvement of nurses; and the safety and quality of care for patients, thereby improving the institutional outcomes (Kouzes & Posner, 2019;Manning, 2016). In this respect, Abou Hashish (2020) and Abou Hashish and Khatab (2018) suggested that nurse managers should be well trained to maintain a caring atmosphere through integrating the Caritas processes and fair treatment and paying more attention to the work activities and behaviors of their nurses.…”
Section: ± 068mentioning
confidence: 99%
“…Leadership was identified as having a major impact on practicing nurses and the perception of a supportive and healthy workplace environment (Kowalski et al, 2020). Behaviors of leaders directly influence their organization's aptitude to attract and maintain the talent of their nurses and are considered a crucial element in achieving competitive benefits in the marketplace (Kouzes & Posner, 2019). Likewise, nurses wield a significant impact on patients and other healthcare team members through knowledge and enactment of professional behaviors such as communication, collaboration, and coordination (Stanley & Stanley, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They create community by recognizing both group accomplishments, and individual contributions to the team's success. Taken together, the specific behaviors reflected in these five practices help leaders to motivate and inspire followers toward cooperation (Kouzes and Posner 2017), and have been used extensively in prior research (e.g., Burkman et al 2019;Caza and Posner 2019;Hage and Posner 2015;Kouzes and Posner 2019;Sherf et al 2020).…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…According to Mas'udah (2019); Zhao et al (2021); Kouzes and Posner (2019); Jach et al (2018) people with a growth mindset believe that failure and challenge are a lesson for the future. They can build positive psychological outcomes and are always optimistic about the future.…”
Section: The Moderating Role Of Growth Mindset On the Effect Of Subje...mentioning
confidence: 99%
“…According to Mas'udah (2019); Anggayani and Hartawan (2019); Kouzes and Posner (2019); Jach et al (2018); Zhao et al (2021), a growth mindset is a mindset that believes that a person's abilities and psychology will develop when they face a problem and try to solve it because they see a challenge as an opportunity to learn so that they are always optimistic about the future and always confident in solving problems. Anggayani and Hartawan (2019) stated that optimism enables a person to assess stressful events more positively and helps mobilize resources to take steps to deal with stressors.…”
Section: Introductionmentioning
confidence: 99%